THE ROLE OF PHYSICAL ACTIVITY IN MODULATING THE GUT MICROBIOTA AND ITS CONSEQUENCES FOR INTESTINAL HOMEOSTASIS AND METABOLISM - A SYSTEMATIC REVIEW - Magdalena Mida,; Magdalena Michalik,; Urszula Majda,; Anna Maruszak,; Julia Kwiecień,; Julia Stołtny,; Justyna Goryczka,; Magdalena Lisik,; Witold Kimla,; Natalia Hajok, (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: The gut microbiota is increasingly recognised as an important regulator of immune function, metabolic processes, intestinal barrier integrity, and gut–brain communication. Both lifestyle factors and dietary habits, including the intake of fermented foods and probiotics, have been shown to influence its composition.Objective: Our aim is to demonstrate how exercise can increase gut microbial diversity, which can be beneficial for athletes' performance, exercise capacity and recovery.Materials and methods: The study is based on a variety of analyses from 1997 to 2026 that were found using PubMed and Google Scholar.Results: Regular physical activity is associated with increased gut microbiota diversity, including a higher abundance of bacteria such as Akkermansia, Veillonella, Prevotella, Bifidobacterium, and Lactobacillus. These changes are linked to improved intestinal function, enhanced athletic performance, and more efficient muscle recovery. In contrast, prolonged or excessive high-intensity exercise may impair intestinal integrity and contribute to dysbiosis.Conclusion: Physical activity promotes a greater diversity of gut microbiota, which can improve bowel function, athletic performance, muscle recovery and appetite regulation. However, the available evidence suggests that training load and recovery strategies should be carefully balanced to avoid potential negative effects on gastrointestinal health.